(NwSE STRANY MIRAs (N|NCIKLOPEDI^ESKIJ SPRAWO^NIK(B.s - (NrODIN(B, (Ni(B.(No(B.s; (NpIMENOWA(B, (Nt(B.(Nm(B.s ((NmOSKWA(B:s (NwE^E(B,s, 2002)
[ (NsPRAWO^NIK WKL@^AET W SEBQ WSE OSNOWNYE SWEDENIQ PO GEOGRAFII(B, (NISTORII(B, (NKULXTURE(B, (N\KONOMIKE(B, (NPRIRODE(B, (NGOSUDARSTWENNOMU USTROJSTWU I WEROISPOWEDANI@ WSEH STRAN (B].s
Keywords: (N|NCIKLOPEDI^ESKIJ SPRAWO^NIKs; (NsTRANY MIRAs; (NgEOGRAFIQs; (NiSTORIQs; (NkULXTURAs; (N|KONOMIKAs; (NpRIRODAs; (NgOSUDARSTWENNOE USTROJSTWOs; (NwEROISPOWEDANIEs